Human Traffickers’ Fair Trial Rights and Transnational Criminal Law - Harré, Thomas (Anti-Trafficking Review, 2022)
The right to a fair trial is enshrined in international and domestic law around the world. This article makes the simple argument that the focus on the rights of victims of human trafficking and efforts to increase the rate of prosecutions of human traffickers should not come at the cost of alleged traffickers’ rights to a fair trial, as a failure to uphold fair trial rights places them at risk of unfair prosecution. I consider the extent to which the transnational criminal legal regime regulating human trafficking at the international level provides for these fair trial rights, suggest that the fundamental purposes of transnational criminal law exist in a state of tension against the aims of the international human rights regime, and conclude that further empirical research on the legal experiences of human traffickers is necessary.